Journalism ethics at the crossroads democracy, fake news, and the news crisis - Patching, Roger 1944-; Hirst, Martin (Routledge, 2022)
This book provides journalism students with an easy-to-read yet theoretically rich guide to the dialectics, contradictions, problems, and promises encapsulated in the term 'journalism ethics'. Offering an overview of a series of crises that have shaken global journalism to its foundations in the last decade, including the Coronavirus pandemic, the Black Lives Matter movement, and the 2020 US presidential election, the book explores the structural and ethical problems that shape the journalism industry today. The authors discuss the three principle existential crises that continue to plague the news industry: a failing business model, technological disruption, and growing public mistrust of journalism. Other topics covered include social media ethics, privacy concerns, chequebook journalism, as well as a new analysis of journalism theory that critiques the well-worn tropes of objectivity, the Fourth Estate, freedom of the press, and the marketplace of ideas to develop a sophisticated materialist reimagining of journalism ethics. This is a key text for students of journalism, mass communication, and media ethics, as well as for academics, researchers, and communications professionals interested in contemporary journalism ethics"--